2023
DOI: 10.3390/nu15173768
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomic Analysis of Lactation-Stage-Matched Human and Bovine Milk Samples at 2 Weeks Postnatal

Dominick J. Lemas,
Xinsong Du,
Bethany Dado-Senn
et al.

Abstract: Epidemiological data demonstrate that bovine whole milk is often substituted for human milk during the first 12 months of life and may be associated with adverse infant outcomes. The objective of this study is to interrogate the human and bovine milk metabolome at 2 weeks of life to identify unique metabolites that may impact infant health outcomes. Human milk (n = 10) was collected at 2 weeks postpartum from normal-weight mothers (pre-pregnant BMI < 25 kg/m2) that vaginally delivered term infants and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The code for reproducing the process of automated workflow composition in this study can be found at: . We used the data collected for our previous milk metabolomics study to illustrate a traditional workflow for the following three use cases . Example data acquisition and analysis results for use cases can be found in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The code for reproducing the process of automated workflow composition in this study can be found at: . We used the data collected for our previous milk metabolomics study to illustrate a traditional workflow for the following three use cases . Example data acquisition and analysis results for use cases can be found in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…In recent decades, omics technologies have been applied as ‘holistic’ add-on techniques to traditional (single-factor) milk bioactivity research in the natural sciences. Genomic analyses of milk and infant cells are used to identify the breast milk miRNA regulators that affect immune maturation [ 98 ], transcriptomics to assess the expressions of milk stem cells and host gene expressions [ 110 ], proteomics and peptidomics to characterize all milk proteins and host cell protein responses [ 111 ], epigenomics to explore the (longer-term) effects of milk on host gene expressions [ 112 ], metabolomics to assess interactions with milk or host metabolites [ 113 ], and microbiomics to assess the interactions between milk and host microbes [ 114 ]—just to mention a few examples. Such techniques, and the wealth of new data they contribute, provide a broader picture of milk components and their multiple effects on the human body.…”
Section: Milk Protein Bioactivity and Human Health Interactionsmentioning
confidence: 99%